Factors influencing halal awareness on food consumptions among Muslim consumers in Malaysia / Nur Farahin Mohamad Fauzi - Mohamad Fauzi, Nur Farahin (Faculty of Business and Management, 2018)
The purpose of this research is to examine the factors influencing halal awareness on food consumptions among Muslim consumers in Malaysia that might be one of the most significant variable of Shariah law. One of the aims of this study is to cover back the limitations of previous studies that did not include main factors that influencing halal awareness on food consumptions as it only focused on halal certification logo only. This study attempts to observe the factors that influence relationship between the factors which are halal exposure, religious belief, health reason, halal certification and halal awareness as well as establish the significance of each factor in predicting halal awareness on food consumptions. Primary data was collected personally from the respondents through questionnaire by distributing to the Muslim consumers in Malaysia. Statistical Programme for Social Sciences (SPSS) was used to analysis the data. Analysis was done to achieve the objectives of this study which are to identify the level of halal awareness on food consumptions, to identify the significant relationship between halal exposure, religious belief, health reason and halal certification with halal awareness and to identify the most influential factor towards halal awareness. Based on the research findings, all variables (halal exposure, religious belief, health reason, and halal certification) are positively significant with halal awareness. Lastly, the researcher hope that this study will help Muslims consumer in Malaysia to be more aware of halal foods.